Policy Implementation of Parking Implementation In Pekanbaru City, Riau Province - Yuliarso, Yuliarso; Averus, Ahmad; Ilham, Muh.; Daraba, Dahyar (Asian Journal of Social and Humanities, 2024)
The aim of this research is to analyze the implementation of parking management policies in Pekanbaru City, the obstacles faced in implementing parking management policies in Pekanbaru City and the ideal and effective policy implementation model for parking management in Pekanbaru City. This research uses the policy implementation theory proposed by Smith which consists of idealized policy, target groups, implementing organization and environmental factors. The research method used is a qualitative approach with descriptive research type. The data analysis technique used is data reduction and drawing conclusions. The results of the research show that the implementation of local government policies in organizing parking in Pekanbaru City has gone well, this can be seen from: idealized policy, proper parking management in Pekanbaru City is able to support the existing transportation system, target groups, very closely related to taking decisions that involve many people, especially the community. implementing organizing, this difference in capacity and competency is one of the aspects that makes the implementation of this policy not optimal. Environmental factors, the obstacle for the Pekanbaru City Parking UPT is the lack of qualified human resources. Barriers to implementing parking policies in Pekanbaru City: commitment to service quality, quality of human resources for government officials and parking attendants, well-developed public communication.